{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

propagating V3

# propagating V3 - ∆ x/x = ∆ F/F Now back to the original...

This preview shows page 1. Sign up to view the full content.

Lots of questions on propagating V3 so here’s the answer… I told some people incorrectly but will bot count off for that mistake. V 3 = (F/ μ ) 1/2 we need to apply a couple of rules for this one First we need to handle the stuff inside the ( ) Let x = F/ μ this is a division which is rule 3 So x /x = (( F/F) 2 +( ∆μ / μ ) 2 ) ½ Now ∆μ = 0 because it is a constant so the second term drops out x /x = (( F/F) 2 +0) ½ The square and the square root cancel each other so
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ∆ x /x = ∆ F/F Now back to the original equation V 3 = (F/ μ ) 1/2 lets rewrite this as V 3 = (x) 1/2 this falls under the power rule number 4 So ∆ v 3 /v 3 =[ (1/2)( ∆ x /x) 2 ] 1/2 Putting our F’s back in ∆ v 3 /v 3 =[ (1/2)( ∆ F /F) 2 ] 1/2 Then ∆ V 3 =V 3 *[ (1/2)( ∆ F /F) 2 ] 1/2 or I can expand it to ∆ V 3 =(F/ μ ) 1/2 [ (1/2)( ∆ F /F) 2 ] 1/2 Hope this helps!...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online